(3GdQjGV ddWHGWHGFjs - (3GdWHGWHGFj, GdcGXej, GdMGFQj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs ((3GdeDdas)
(3ChdgG (B:s
(3HSe Gddg (B.. (3hgh aj GddZI deYGf cKjQI GdNdb hefg bhdg Gfg (B" (3abVGgf SHY SeGhGJ (B" (3Cj Ndbgf hGdMce hefg bhdg JYGdi (B" (3Gddg jbVj HGdMb (B" (3Cj jMce hGdCeQ hefg bhdg YR ef bGFd (B...s
(3BNQgG (B:s
.. (3hjNJU VeGfgG Cj GdYGbdI HGdLfGjI eef JYbd Yfg Ydi GdBOej aMSH HdG NdGa aj TjA ef Pdc CLOg ddCUd eY GNJUGU eG Od Ydi VeGf GdYGbdI ef GdaJhi (B.. (3agPG eG ChQOfGgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3EjVGM Gdecfhf (B1\ 603s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis